Environmental Valuation with Discrete Choice Experiments Guidance on Design, Implementation and Data Analysis - Mariel, Petr; Hoyos, David; Meyerhoff, Jürgen; Czajkowski, Mikolaj; Dekker, Thijs; Glenk, Klaus; Jacobsen, Jette Bredahl; Liebe, Ulf; Olsen, Søren Bøye; Sagebiel, Julian; Thiene, Mara (SpringerBriefs in Economics, 2021)
This open access book offers up-to-date advice and practical guidance on how to undertake a discrete choice experiment as a tool for environmental valuation. It discusses crucial issues in designing, implementing and analysing choice experiments. Compiled by leading experts in the field, the book promotes discrete choice analysis in environmental valuation through a more solid scientific basis for research practice. Instead of providing strict guidelines, the book helps readers avoid common mistakes often found in applied work. It is based on the collective reflections of the scientific network of researchers using discrete choice modelling in the field of environmental valuation (www.envecho.com).